PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII MTsN 2 KOTA PAYAKUMBUH - Muliana, Sri (Jurnal Edukasi dan Penelitian Matematika, 2023)
Communication skills in mathematics are very important for students. However, in real life the mathematical communication skills of class VII MTsN 2 Kota Payakumbuh students for the 2022/2023 academic year are not yet satisfactory. This can be reviewed through the results of the initial test of mathematical communication skills presented to students. Efforts to achieve improvements in students' mathematical communication skills include implementing a cooperative learning model with the TPSq (Think Pair Square) type. The type of research used is quasi experimental research using a Static Group Design research design. The technique for obtaining samples was carried out through Simple Random Sampling. The final test in essay form is the instrument used. The process of proving the hypothesis of this research is through the use of the t-test. P-value = 0.028 < ? = 0.05, meaning ?0 is rejected. Then, a conclusion can be reached that the mathematical communication abilities of students who take part in the learning process using the TPSq type cooperative model are superior to the mathematical communication abilities of students who take part in the learning process using the direct learning model.Keywords– Mathematical Communication Abilities, Cooperative Learning Model Type Think Pair Square